Identification of the "4 A" Potential in Developing the Tourist Attraction of Jaga Satru Waterfall in East Duda Village, Karangasem District - AMERTA, I Made Suniastha; PUTRA, Ida Bagus Udayana; ARTANA, I Wayan Santi; DARMAWAN, Anak Agung Rai (International Journal of Environmental, Sustainability, and Social Science, 2024)
International tourism trends are shifting towards unconventional destinations like rural areas for their serene ambiance, contrasting with traditional spots. This prompts research, particularly at Jaga Satru Waterfall, to assess its tourist appeal and potential. The study aims to evaluate the "4A" potential for developing Jaga Satru Waterfall as a tourist site, along with devising general and alternative strategies. The study involves tourists, tourism managers, government officials, community leaders, and locals. Purposive Sampling was employed with a sample size of 30 individuals. Data analysis utilized the Internal External Matrix, SWOT Analysis Diagram, and SWOT Matrix. The research results show: The attractions include the Jaga Satru waterfall, views of Nyegara-Mountain Nature, the tallest statue of God Brahma in Bali and the Sudamala Emblemishing site. Accessibility is quite good even though there are curves and inclines when accessing the area and visitors have to climb down 160 steps with bamboo and iron guards. Amenities are quite good but need to be improved, such as parking area facilities, public toilets/toilets, and restaurants and relaxing areas. Ansilari, namely the official village, has formed a Tourism Awareness Group (POKDARWIS). POKDARWIS in this village is under the coordination of the Pateh traditional village head. General strategies include the management of the Jaga Satru Waterfall DTW needing to improve road access to this area and add various tourism facilities such as souvenir shops and information centers for tourists. Alternative strategies for developing the Jaga Satru Waterfall DTW are implemented in 4 SWOT strategies.